2021
DOI: 10.1097/cd9.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Cartilage Oligomeric Matrix Protein and Bone Morphogenetic Protein-2 May Associate with Calcific Aortic Valve Disease

Abstract: Objective: Calcific aortic valve disease (CAVD) affects millions of elderly people, and there is currently no effective way to stop or slow down its progression. Therefore, exploring the pathogenesis of CAVD is very important for prevention and treatment. Cartilage oligomeric matrix protein (COMP) have important role in cell phenotype change. This study is aimed to confirm whether COMP participate in CAVD and try to find the possible mechanisms.Methods: Human aortic valve tissues from Nanjing First Hospital (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Cartilage oligomeric protein (COMP) and alpha 2-Heremans-Schmid glycoprotein (AHSG) were among the 6 VIC upregulated proteins. COMP has been reported to be expressed higher in calcific valve samples near calcific nodules in calcific aortic valve disease patients ( Xu et al, 2021 ) and AHSG was shown to be an inhibitor of ectopic calcification ( Schäfer et al, 2003 ). Furthermore, we also found some previously identified valve ECM proteins, including hyaluron-1 and fibrillin-2, to have a VIC/LVCFBs abundance ratio greater than 1, but these showed variability in magnitude between donor samples ( p -values 0.25 and 0.77 respectively) ( Lockhart et al, 2011 ; Wiltz et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage oligomeric protein (COMP) and alpha 2-Heremans-Schmid glycoprotein (AHSG) were among the 6 VIC upregulated proteins. COMP has been reported to be expressed higher in calcific valve samples near calcific nodules in calcific aortic valve disease patients ( Xu et al, 2021 ) and AHSG was shown to be an inhibitor of ectopic calcification ( Schäfer et al, 2003 ). Furthermore, we also found some previously identified valve ECM proteins, including hyaluron-1 and fibrillin-2, to have a VIC/LVCFBs abundance ratio greater than 1, but these showed variability in magnitude between donor samples ( p -values 0.25 and 0.77 respectively) ( Lockhart et al, 2011 ; Wiltz et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%